Decadal Shift in West China Autumn Precipitation and its Association With Sea Surface Temperature. Issue 2 (23rd January 2018) - Wei, Ting; He, Shengping; Yan, Qing; Dong, Wenjie; Wen, Xiaohang
Abstract: West China autumn precipitation (WCAP) is the final stage of the rainy season in mainland China and is characterized as the secondary peak in annual cycle of precipitation in West China. This study reveals that WCAP experienced a significant interdecadal shift around the mid‐1980s, with greatly reduced precipitation after this shift. Features related to the decrease in WCAP include the weakening of warm, wet southerlies prevailing from the oceans to inland China, the weakened Eurasian pattern, and the southward displacement of the East Asian jet stream (EAJS). Further analysis indicates that the interdecadal changes in WCAP may be attributed to the interdecadal increasing of sea surface temperature (SST) in the Indo‐Pacific warm pool (SSTIOP ), North Pacific (SSTNP ), and central equatorial Pacific (SSTCEP ) after the 1980s. The warmer SSTIOP contributes to a weaker meridional land‐sea thermal contrast, which inducts an anomalous local meridional circulation and northerly. The warmer SSTNP stimulates a Rossby wave train that leads to weakened West Pacific subtropical high and accompanying cyclonic circulation anomaly, hindering the transport of water vapor inland from the oceans. The increased SSTCEP leads to the southward displacement of the EAJS and its secondary circulation, generating an anomalous descending branch and reduced WCAP. Numerical simulations further support the conclusions derived from the diagnostic analysis that the decadal warming of the SSTIOP, SSTNP, and SSTCEP synergistically contributes to the reduction of WCAP after the 1980s. Key Points: The West China autumn precipitation (WCAP) experienced a significant interdecadal shift around the mid‐1980s The shift of WCAP is attributed to the interdecadal warming in the Indo‐Pacific warm pool, North Pacific, and central equatorial Pacific Numerical simulations confirm the synergistic contributions of the three ocean regions